A comparative analysis of the health-related consequences of drought in the Po and Colorado river basins - Carter, Christopher Alan (Kansas State University, 2024)
Global climate change will continue to expose more communities to drought, a prominent environmental health hazard. Droughts, directly and indirectly, affect the health of nearby communities through reduced air and water quality, increased incidence of infectious disease, malnutrition, and poor mental health. Two regions in Europe and the United States faced with drought, the Po River Basin and the Colorado River Basin, provide an opportunity to understand how geography and policy affect the prevalence of the health-related consequences of drought. This thesis quantifies the drought conditions and relevant health-related consequences of drought in both the Po and Colorado River Basins to argue for the most salient public health challenge in each region. In the Po River Basin, heavy industry and natural geography render poor air quality the most salient challenge, and in the Colorado River Basin, the emerging disease coccidioidomycosis poses the most salient risk. By identifying the most salient health-related consequence of drought, public health practitioners and policymakers may more effectively target public health interventions and policies to reduce the burden of drought on public health.
Keywords: Drought; Public health; Water; Vector-borne disease; Air quality; Valley fever